Evaluation of nematicidal potential in ten indigenous plant species against Meloidogyne incognita - GUNANIDHI BEHERA, N.N. PADHI and (Indian Phytopathology, 2002)
In vitro studies on hatching and mortality of second-stage juveniles of Meloidogyne incognita indicated a reduction in hatching and an increase in nematode mortality in treatments with aqueous leaf extracts of seven plant species; Murraya koenigii (curry leaf), Jasminum sambac (Jasmine), Citrus aurantiifolia (sour orange), Rauvolfia serpentina (patal garuda), Zizyphus jujuba (ber), Hibiscus rosa-sinensis (china rose) and Justicia gandurosa [J. gendarussa]. Organic amendment with powdered leaves ofthe plants at 3% w/w in soil infested with M. incognita 3 weeks before transplanting tomato (cv. Pusa Ruby) seedlings reduced nematode infection and increased plant growth in comparison with the control. Although the plant species Gmelina arborea (gambhar), Madhuca latifolia [Madhuca longifolia] (mahula) and Callistemon lanceolatus [Callistemon citrinus] (bottle brush) also possessed nematicidal properties, they adversely affected the growth of tomato plants.